Advanced glow curve analysis of fabricated fibres for various sources of ionizing radiation - Kandan, V.; Hassan, M.F.; Omar, N.; Shahar, H.K.; Mohamad, F.; Abdul Karim, M.K.; Abdul Sani, S.F.; Bradley, D.A. *; Mohd Noor, N. (Elsevier, 2021)
Determination is made of glow curves attributes of Ge-doped silica fibres fabricated from Ge-doped preforms. In particular interest is in Ge-doped cylindrical (Ge-CF) and Ge-doped flat (Ge-FF). The fabrications are irradiated using various ionizing radiation sources types, protons (150 MeV, 210 MeV), 6 and 10 MV photons, 6 MeV electrons, and 60Co gammas (mean energy 1.25 MeV), all at a constant dose of 5 Gy. The fibres have been fabricated using the MCVD technique, notably with a Ge-CF having a larger core compared to the commercial cylindrical fibres (CF). Using WinGCF software the glow curves have been deconvolved, revealing five contributory glow peaks, evaluation being made of three kinetic parameters: maximum temperature (Tmax), activation energy (Ea) and peak integral (PI). Ge-CF Ea and PI values are found to be greater than those for Ge-FF. Moreover, for Ge-CF, the activation energy for electromagnetic irradiation (gamma photons) achieves a maximum reading at peak number 3 while its PI is found to be the least. The PI for photon irradiation is shown to be greater than that for electron and proton irradiation. For Ge-FF, Ea again achieves its greatest value at peak 3, the PI being maximum at peak 2 and least at peak 3. Particle irradiations are more greatly associated with deeper trapping levels. Additionally, the overall conclusion is that Ge-CF offers superior TL yield to that of Ge-FF. One-way analysis of variance (ANOVA) for the individual peaks shows there to be significant differences in terms of PI and Ea, p < 0.05 for all types of radiation, but weakly significant in terms of Tmax for both types of fibres (p < 0.05), mostly for proton and photon irradiation.